ANALISIS PENERAPAN PSAK NO. 45 (REVISI 2011) TENTANG PELAPORAN KEUANGAN ENTITAS NIRLABA PADA YAYASAN LEMBAGA KONSUMEN INDONESIA (YLKI) - Bumulo, Regina Amalia; Mogi, Grace B.; Sabijono, Harijanto (Universitas Sam Ratulangi, 2014)
Foundation is one form of a non-profit entity that aims to provide services to the public community without seeking advantage in carrying out its activities. The legal form of the foundation is often used as a shield to enrich the Founders, the Controllers, and the Directors. To minimize this, and in order to implement the principles of transparency and accountability to the public, the foundation should do the publication of its financial statements in accordance with the current SAK in Indonesia, the PSAK No. 45 (Revised 2011). The purpose of this study is to analyze the financial statements of the Indonesian Consumers Organization in accordance with PSAK No. 45 (Revised 2011). In this study, the author analyzed the data by collecting, interpreting, and analyzing it to produce conclusions about the true state, then compare it with PSAK No. 45 (Revised 2011). Based on the analysis and evaluation can be concluded that: (1) In the statement of financial position, there is no separation between current liabilities and long term liabilities. Also there is a mismatch use of the term